Myconanotechnology and application of nanoparticles in biology : fundamental concepts, mechanism and industrial applications - Kuddus, Mohammed; Ahmad, Iffat Zareen; Hussain, Chaudhery Mustansar (Progress in biochemistry and biotechnology, 2023)
"Myconanotechnology and Application of Nanoparticles in Biology: Fundamental Concepts, Mechanism and Industrial Applications focuses on the emergence of myconanotechnology as a new science for the synthesis of nanoparticles using fungi and considering future applications and challenges. The book demonstrates why mycology should be regarded as a megascience: A subject requiring international collaboration to overcome barriers that need to be confronted in the interests of global security and human well-being. This reference provides a good source of knowledge and guidelines for advanced graduate students and will be of significant interest to scientists working on the basic issues surrounding applications of myconanotechnology." --